Inmigración, interculturalismo e proceso educativo: a escola como vector estratéxico - Miguel Anxo Rego Santos (Universidade do Minho, 2000)
This article deals with school as a strategic vector in countries like Portugal and Spain, where inmigrant population has increased in the last years. This change of tendency in relation with migration flows, included historic and socio-political determinants, results in another view about school and about its role in the desirable strenghtening of civil society in this part of European Union. Among other aspects, we pay attention to the induced link between inmigration and conflict, the dialectical proximity of the inmigration reality and intercultural discourse. Finally, we pose the need to articulate, in inclusive terms, a valid educational intervention.